Opium smoking suppression campaigns and the role of anti-opium movements in the Federated Malay States, 1906-1910 - Jayakumary Marimuthu,; Mohd Firdaus Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article studies the history of opium smoking and anti-opium movements in Federated Malay States (FMS). By the end of the 17th century, the Chinese community consituted the majority of opium smokers due to the British and Chinese capitalists greed to gain profits through the rapidly growing opium trading. The emergence of anti-opium movements in FMS was triggered by a number of key elements such as the development of anti-opium movement in Britain and China, and the spirit of nationalism among local Malayan Chinese towards their Mainland China which was gradually weakening due to escalating number of opium problems. Spearheaded by Chinese capitalists and a few Europeans, the anti-opium movement was transformed into several anti-opium organizations that carried out various initiatives to suppress the opium smoking habits. This study found that the anti-opium movement in FMS had played an important role in influencing the British government to change its view and policies on trade and smoking opium habit by 1910.